2023
DOI: 10.1007/s44246-023-00043-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biochar and biofertilizer on groundnut production: a perspective for environmental sustainability in Bangladesh

Abstract: Regular large-scale application of fertilizers, pesticides, and mulching can lead to soil health degradation and increase negative environmental impacts, contributing significantly to greenhouse gas (GHG) emissions. Considering these factors by applying biochar and biofertilizer (rhizobium inoculants) in groundnut production, a novel experiment was conducted for increasing soil fertility, groundnut productivity, and soil carbon stock in Bangladesh's Charland agroecosystems. The two-year experiment involved sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…In another study, soil invertase activity positively correlated with SOC, available phosphorus, and nitrogen (Bamdad et al, 2022). Pathy et al (2020) reported increased phosphatase activity with biochar application, indicating an increased fraction of bioavailable P (Shikha et al, 2023). Aboughaly and Fattah (2023) showed that almond-derived biochar positively impacted urease and dehydrogenase activities.…”
Section: Soil Enzyme Activitymentioning
confidence: 95%
“…In another study, soil invertase activity positively correlated with SOC, available phosphorus, and nitrogen (Bamdad et al, 2022). Pathy et al (2020) reported increased phosphatase activity with biochar application, indicating an increased fraction of bioavailable P (Shikha et al, 2023). Aboughaly and Fattah (2023) showed that almond-derived biochar positively impacted urease and dehydrogenase activities.…”
Section: Soil Enzyme Activitymentioning
confidence: 95%
“…Once saltmarshes are degraded, the liable organic carbon stored in the sediment is preferentially to be decomposed and released as greenhouse gases (Yang et al 2021;Rahman et al 2021). Currently, biochar is widely considered as an effective soil amendment for mitigating climate change (Jiang et al 2023;Shikha et al 2023). Therefore, we suspect that adding biochar to saltmarshes would also alleviate the increasing global warming potential of saltmarsh degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we suspect that adding biochar to saltmarshes would also alleviate the increasing global warming potential of saltmarsh degradation. Biochar is a carbon-rich and porous material produced by pyrolysis or hydrothermal carbonization of biomass (Feng et al 2022), and it contains approximately more than 50% carbon that can be stably stored in the soil (Shikha et al 2023). Moreover, biochar has been demonstrated to alter the soil microbial community structure (Ma et al 2023;Qiu et al 2023), which could indirectly affect the mineralization and immobilization of soil organic carbon (SOC) (Qiu et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The 3Rs—reduce, reuse, and recycle—contribute to long-term environmental development. Because forestry wastes are abundant in biomaterials, if employed, they might become the backbone of sustainable development, producing a variety of opportunities for future generations 30 . Carrasco et al 31 carried out a pyrolysis test using Maine forest residues.…”
Section: Introductionmentioning
confidence: 99%